Synthesis and biological evaluation of 2-styrylquinolines as antitumour agents and EGFR kinase inhibitors: molecular docking study - Magda A.-; Walaa M. El-Husseiny; Naglaa I. Abdel-Aziz; Adel S. El-Azab; Hatem A. Abuelizz; Alaa A.-M (Taylor & Francis Group, 2018)
A new series of 4,6-disubstituted 2-(4-(dimethylamino)styryl)quinoline 4a,b-9a,b was synthesized by the reaction of 2-(4-(dimethylamino)styryl)-6-substituted quinoline-4-carboxylic acids 3a,b with thiosemicarbazide, p-hydroxybenzaldehyde, ethylcyanoacetate, and 2,4-pentandione. In addition, the antitumour activity of all synthesized compounds 3a,b-9a,b was studied via MTT assay against two cancer cell lines (HepG2 and HCT116). Furthermore, epidermal growth factor receptor (EGFR) inhibition, using the most potent antitumour compounds, 3a, 3b, 4a, 4b, and 8a, was evaluated. The interpretation of the results showed clearly that the derivatives 3a, 4a, and 4b exhibited the highest antitumour activities against the tested cell lines HepG2 and HCT116 with IC50 range of 7.7-14.2 µg/ml, in comparison with the reference drugs 5-fluorouracil (IC50 = 7.9 and 5.3 µg/ml, respectively) and afatinib (IC50 = 5.4 and 11.4 µg/ml, respectively). In vitro EGFR screening showed that compounds 3a, 3b, 4a, 4b, and 8a exhibited moderate inhibition towards EGFR with IC50 values at micromolar levels (IC50 range of 16.01-1.11 µM) compared with the reference drugs sorafenib (IC50 = 1.14 µM) and erlotinib (IC50 = 0.1 µM). Molecular docking was performed to study the mode of interaction of compounds 3a and 4b with EGFR kinase.